Minority policy and sociology in German and Polish democracy in the interwar period = Polityka wobec mniejszości a socjologia w Niemczech i Polsce w okresie międzywojennym - Messerschmidt, Nadja (Zielona Góra: Lubuskie Towarzystwo Naukowe)
My subject opens up the field of Interwar Period Sociology for further research. In this paper I would like to begin by giving some known historical facts for the installation of new sociological institutes in Interwar Period in German Reich and Poland too. Secondly, I would like to discuss some main German studies in this scientific field.
Keywords: mniejszości; socjologia; Niemcy; Polska; 1918-1939